2018
DOI: 10.1097/md.0000000000013645
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of methylenetetrahydrofolate reductase C677T and risk of ischemic stroke in a southern Chinese Hakka population

Abstract: Previous studies have shown that methylenetetrahydrofolate reductase (MTHFR) gene to be a genetic risk factor for the susceptibility to ischemic stroke. The aim of this case-control study was to investigate whether the polymorphisms of MTHFR C677T were associated with the susceptibility to ischemic stroke in a southern Chinese Hakka population. In this study, a total of 1967 ischemic stroke patients and 2565 controls of Chinese Hakka ethnicity were recruited. The MTHFR C677T polymorphisms were genotyped by pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“… Reference citations: [ 83 ], [ 73 ], [ 86 ], [ 60 ], [ 81 ], [ 57 ], [ 72 ], [ 53 ], [ 88 ], [ 67 ], [ 39 ], [ 84 ], [ 64 ], [ 48 ], [ 75 ], [ 38 ], [ 94 ], [ 65 ], [ 93 ], [ 47 ], [ 77 ], [ 61 ], [ 35 ], [ 15 ], [ 90 ], [ 37 ], [ 52 ], [ 92 ], [ 45 ], [ 89 ], [ 91 ], [ 49 ], [ 31 ], [ 95 ], [ 50 ], [ 71 ], [ 78 ], [ 32 ], [ 87 ], [ 66 ], [ 33 ], [ 59 ], [ 62 ], [ 36 ], [ 74 ], [ 76 ], [ 34 ], [ 63 ], [ 70 ], [ 68 ], [ 58 ], [ 80 ], [ 51 ], [ 79 ], [ 42 ], [ 56 ], [ 40 ], [ 44 ], [ 55 ], [ 82 ], [ 54 ], [ 46 ], [ 43 ], [ 69 ], [ 41 ], [ …”
Section: Reviewunclassified
See 1 more Smart Citation
“… Reference citations: [ 83 ], [ 73 ], [ 86 ], [ 60 ], [ 81 ], [ 57 ], [ 72 ], [ 53 ], [ 88 ], [ 67 ], [ 39 ], [ 84 ], [ 64 ], [ 48 ], [ 75 ], [ 38 ], [ 94 ], [ 65 ], [ 93 ], [ 47 ], [ 77 ], [ 61 ], [ 35 ], [ 15 ], [ 90 ], [ 37 ], [ 52 ], [ 92 ], [ 45 ], [ 89 ], [ 91 ], [ 49 ], [ 31 ], [ 95 ], [ 50 ], [ 71 ], [ 78 ], [ 32 ], [ 87 ], [ 66 ], [ 33 ], [ 59 ], [ 62 ], [ 36 ], [ 74 ], [ 76 ], [ 34 ], [ 63 ], [ 70 ], [ 68 ], [ 58 ], [ 80 ], [ 51 ], [ 79 ], [ 42 ], [ 56 ], [ 40 ], [ 44 ], [ 55 ], [ 82 ], [ 54 ], [ 46 ], [ 43 ], [ 69 ], [ 41 ], [ …”
Section: Reviewunclassified
“…No Subgroup -Asian studies: [85], [41], [69], [43], [46], [54], [82], [55], [44], [56], [80], [70], [63], [76], [66], [87], [32], [78], [71], [95], [91], [89], [92], [52], [90], [15], [61], [47], [93], [94], [75], [64], [88], [53], [72], [57], [60], [86], [73], [83].…”
Section: Smentioning
confidence: 99%
“…Earlier scienti c investigations have revealed that the MTHFR C677T gene polymorphism is a genetic risk factor associated with an increased human susceptibility to develop CVDs (Hou et al 2018;Lakkakula 2019;P.-F. Liu et al 2020). Hou et al (2018) completed a case-control study on the association between MTHFR C677T polymorphism and the predisposition to ischemic stroke in a Southern Chinese Hakka population (n=4532).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier scienti c investigations have revealed that the MTHFR C677T gene polymorphism is a genetic risk factor associated with an increased human susceptibility to develop CVDs (Hou et al 2018;Lakkakula 2019;P.-F. Liu et al 2020). Hou et al (2018) completed a case-control study on the association between MTHFR C677T polymorphism and the predisposition to ischemic stroke in a Southern Chinese Hakka population (n=4532). The results showed an expanded risk of ischemic stroke in the homozygous polymorphic TT genotype group compared to the homozygous CC genotype and heterozygous CT genotype groups, even after adjusting for traditional risk elements (Hou et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…13 Previous studies showed that the MTHFR C677T gene polymorphism among ischemic stroke patients was relatively high, including in the Indonesian population, ranging from 13.9-40.3% for the CT genotype and 3.2-7.0% for the TT genotype. [14][15][16] In general, the variation in the prevalence of these gene polymorphisms is strongly influenced by ethnicity. This gene polymorphism will decrease the MTHFR enzyme activity at 37°C or higher and increase blood homocysteine levels.…”
Section: Introductionmentioning
confidence: 99%